Teachers' Emotion and Identity Work During a Pandemic - Jones, Alexis L.; Kessler, Meghan A. (Frontiers in Education, 2020)
Teachers' Emotion and Identity Work During a Pandemic This piece is a conceptual analysis of the care involved on the part of teachers during the COVID-19 era and the relationship it has to teachers’ identities. Using the author’s stories, we address how fatiguing care is on a normal day, not to mention what is involved during the COVID era. This care, and the emotions involved, is closely tied to teachers’ identities, calling into question how teachers conceptualize their teacherhood during a pandemic. Our hope is that others will consider where they may have misunderstood teachers’ work. We aim to raise awareness of the complexity of teaching and suggest how teacher education can address and support teachers’ needs.